Beauty Construction on Clean&Clear Foaming Face Wash Video Advertisement: A Semiotic Analysis - Haryati; Deni Apriadi (Journal of Pragmatics Research, 2024)
The study attempts to explain and describe the semiotic process and the stereotype about beauty construction in video advertisements. A triadic meaning of semiotics is used to identify and analyze the data, focusing on representamen, object, and interpretant. In addition, this study also uses the theory of beauty stereotypes to identify cultural conflicts in the form of beauty construction in society. The method of this study is descriptive qualitative because the writer collected the data in the form of written words, which produces descriptive information. There are sixteen pictures captured from the "Gak Perlu Curi-curi Lagi Cek" – Clean&Clear Foaming Face Wash video advertisement that was analyzed in this study. The research found that the semiotic elements consisting of representamen, objects, and interpretants appeared in the Clean & Clear video ads. The interpretation of signs in this study shows that women are trapped in a dilemmatic beauty construction where physical appearance is an absolute beauty concept for women. Beauty becomes a stereotype because of the construction made by the advertising media that requires women to have perfect physical appearances: smile, confidence, genetically colored skin, clean, without blemishes and acne.